ALTERSIMEDIS (ALAT TERAPI KANKER MEMANFAATKAN STIMULAN GELOMBAK OTAK ALFA-TETHA TERINTEGRASI DENGAN PEMBANGKIT MEDAN LISTRIK) - Sodiq, Nizar; Basori, Slamet; Widyasari, Puspita; maulana, Satria Imam; Ramadhon, Bagus Dwi (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
Cancer became the second largest contributor to death in the world, after cardiovascular. Cancer therapies such as chemo therapy, has some side effects that can not be underestimated. Electric field with a frequency of 150KHz-300KHz capable of destroying cancer cells without any biological effects that are so meaningful. Trends in the patient after being diagnosed with cancer is loss of control, depression and despair. So the psychological condition of the patient should also get special treatment because of poor emotional state will affect the diet and lifestyle of the patient.Sound is a stimulant of the brain waves. Sound can deliver patients to the condition of the alpha and theta brain waves. Alpha and theta brainwaves can eliminate stress, improve morale and life expectancy of patients, improve the bodys immune and self-healing from within. So we need to design an electric field generating device to destroy cancer cells that is integrated with the brain waves stimulant. With this tool the patient receives treatment for cancer at the same time with psychological therapy. This tool is also relatively easy to use and relatively cheap.Â Â Â Â Â Â Â Â Â Â Â Keyword â kanker, frekuensi, Gelombang otak, stress, psikologis.